2010
DOI: 10.33899/mmed.2010.29083
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue tumors - Histopathological study of 93 cases

Abstract: Objective: Histopathological and immunohistochemical examination of soft tissue tumors to assess the value of these techniques in verifying the primary diagnosis and their classification. Methods: A prospective study of 93 consecutive soft tissue biopsies that reached the department of histopathology, central labs, Dohuk, and application of immunohistochemical markers on 27 biopsies. Results: Out of 93 soft tissue tumors, 70 (75.2%) were benign with mean age 27.6 y. and 23 cases (24.8 %) were malignant with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The mean age of patients with benign tumors was 41.72 years and that of malignant tumors was 51.11 years. On the contrary, in the study by Hassawi et al, 10 the mean age of patients with benign STT was 27.6 years, and in soft-tissue sarcomas, it was 39.1 years. In the present study, out of 152 cases, there were 81 males (53.29 %) and 71 females (46.71%).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The mean age of patients with benign tumors was 41.72 years and that of malignant tumors was 51.11 years. On the contrary, in the study by Hassawi et al, 10 the mean age of patients with benign STT was 27.6 years, and in soft-tissue sarcomas, it was 39.1 years. In the present study, out of 152 cases, there were 81 males (53.29 %) and 71 females (46.71%).…”
Section: Discussionmentioning
confidence: 78%
“…Malignant STT constituted 6.67% of all STT in their study. Another study on 93 soft-tissue tumors by Hassawi et al,10 for a period of 1 year (2007-2008) reported the incidence of benign and malignant soft-tissue tumors as 75.2% and 24.8%, respectively. Intermediate-grade tumors consisted of 2.63% of all soft-tissue tumors in the present study.…”
mentioning
confidence: 99%
“…Abdominal wall endometriosis (AWE) and uterine fibroids (leiomyoma) affect the uterus and occur in females of childbearing age. While leiomyomas are smooth muscle tumors that grow from the uterine wall, AWE is a rare form of extra-pelvic endometriosis, Life 2023, 13, 1485 2 of 12 with the majority of cases occurring after cesarean section or abdominal surgery [3,4]. Desmoid tumors, also known as aggressive fibromatosis, are a rare type of benign STT that arise from fibrous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…When a soft tissue mass arises in a patient with no history of trauma or when a mass persisting even after 6 weeks after a local trauma a biopsy isindicated. They arise nearly everywhere in the body, the most important locations being the extremities, trunk, abdominal cavity and head & neck region [2] . It is sometimes possible to make an accurate diagnosis by detail clinical history, physical examination and naked eye examination of the tumors.…”
Section: Introductionmentioning
confidence: 99%